Molecular docking and dynamics studies show: phytochemicals from papaya leaves extracts as potential inhibitors of SARS–CoV–2 proteins targets and TNF–alpha and alpha thrombin human targets for combating COVID-19 - Abd Shukor, Mohd Shukri; Abd Shukor, Mohd Yunus (AIMS Press, 2023)
Tackling COVID-19 requires halting virus proliferation and reducing viral complications in humans. Papaya leaf extract (PLE) is well known for its ability to inhibit numerous viral replications in vitro and in vivo and reduce viral complications in humans such as thrombocytopenia and cytokine storm. The goal of this research is to evaluate the possible use of papaya leaf extract as a multifaceted antiviral and potential therapy for COVID-19 using an in-silico docking followed by a 100 ns molecular dynamics simulation (MDS) approach. The targeted proteins are the SARS-CoV-2’s proteins such as the nucleocapsid, main protease (MPro), RNA-dependent RNA polymerase (RdRP), spike protein (Wuhan, Delta, and Omicron variants) and human TNF-alpha and alpha-thrombin protein targets. Several compounds from PLE such as protodioscin, clitorin, glycyrrhizic acid, manghaslin, kaempferol–3–(2g–glucosylrutinoside), rutin, isoquercetrin and acacic acid were found to exhibit strong binding to these targets. The free energies of binding (Autodock) with protodioscin, the best PLE compound for nucleocapsid, main protease (MPro), RdRP and spike protein were –13.83, –13.19, –11.62 and –10.77 (Omicron), kcal/mol, respectively, while the TNF-alpha and alphathrombin binding free energies were –13.64 and –13.50 kcal/mol, respectively. The calculated inhibition constants for protodioscin were in the nanomolar and picomolar range at 216.34, 27.07, 73.28, and 99.93 pM, respectively, whilst RdRp and spike protein (Omicron) were in the nanomolar range at 3.02 and 12.84 nM, respectively. Protodioscin interacted with key residues of all protein targets. The binding affinity poses were confirmed by molecular dynamics simulation. Analysis of the binding affinities calculated employing the molecular mechanics-Poisson–Boltzmann surface area (MM-PBSA) shows favorable interaction between protodioscin, and all targets based on total binding-free energies corroborating the Autodock’s docking results. In conclusion, compounds from PLE, especially protodioscin have good potentials in combating COVID-19.